Public policies enabling the social and solidarity economy in the city of Montreal - Marguerite Mendell; Nancy Neamtan; Hyuna Yi (United Nations Research Institute for Social Development (UNRISD), 2020)
The paper describes the development of the social economy in Montreal between 2013 and 2019. In the Canadian political system, the provincial and federal governments play an important role in implementing enabling policies for the social economy, and municipalities have a limited capacity to intervene. This context, however, has not precluded the creation of significant relationships between the social economy and the Montreal municipal government, particularly on a sectoral basis. Following adoption in 2013 by the Quebec National Assembly of framework legislation on the social economy, the period 2013-2019 was characterized by an ongoing process of policy co-construction in Montreal, spearheaded by a diversity of actors. The paper highlights the importance of adopting and maintaining an integrated, ecosystemic approach; of establishing relations based on partnerships and not on the subordination of the social economy to a political agenda or to public administrations; and of integrating the social economy into an overall vision of ecological and social transition in an urban setting. Montreal's social economy enterprises contributed to socioeconomic development in key sectors affecting the quality of life, including housing, culture, sports and recreation, and food systems. Major changes during the period included the development of the social economy in emerging sectors, innovations in traditional sectors, an increased contribution from universities and youth, and intersections with emerging issues such as the circular economy and the commons. According to the authors, Montreal's social economy remained strong and resilient during the period, despite some setbacks at the policy level. The culture of collaboration and collective action that spearheaded the growth of the social economy in the city in recent decades remained vibrant. Looking forward, the mobilization of civil society actors, and particularly youth, in favour of an ecological and social transition may open the door to a new growth spurt in Montreal's social economy.
Keywords: 330; Föderalismus; Stadtentwicklung; Regionalpolitik; Öffentlicher Auftrag; Öffentliche Finanzen; Sozialwirtschaft; Kanada; Montreal